(untitled) (Gaceta Técnica, 2015)
The purpose of this project was to find out the demand for material and performance of concentric and eccentric bracing for possible seismic events in steel ten stories buildings that have identical geometric characteristics as well as on steel structures without bracings. A linear static analysis and a dynamic one were conducted to determine the stresses in the members, to be able to design their different sections in the structures studied. Once these analysis are made it can be determined the maximum displacements between floors. According to the results, it was concluded that the use of both eccentric and concentric bracings is favorable to the structures, as they offer satisfactory performance for controlling the displacement and provide greater lateral stiffness. The structures which are not braced are the most susceptible to damage in seismic events, which must be analyzed in detail, presenting in turn increased demand for material